2023
DOI: 10.1039/d3cp00974b
|View full text |Cite
|
Sign up to set email alerts
|

Lithium storage performance enhanced by lithiation-induced structural phase transitions of fluorinated MXenes

Abstract: Structural phase transitions in electrode materials of Li-ion batteries (LIBs) often occur along with Li-ion extraction/intercalation during charge and discharge processes. Lithiation-induced phase transition behaviors of two-dimensional fluorinated MXenes were...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 85 publications
0
7
1
Order By: Relevance
“…Our calculated results are consistent with previous studies about several M 2 CS 2 . 21,22,25–27,57 The most stable locations of S functional group for all the M 2 C are consistent with those of O functional group, 45,47 however differ somewhat from F functional group, in which FCC configuration is the most stable for nearly all the M 2 C. 46…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Our calculated results are consistent with previous studies about several M 2 CS 2 . 21,22,25–27,57 The most stable locations of S functional group for all the M 2 C are consistent with those of O functional group, 45,47 however differ somewhat from F functional group, in which FCC configuration is the most stable for nearly all the M 2 C. 46…”
Section: Resultsmentioning
confidence: 59%
“…37–39,42–44 Compared to numerous studies on the Li storage performance, research on the phase transitions of MXene electrodes during Li-ion intercalation is relatively limited. Previous theoretical studies 45–47 reported that structural phase transitions of MXene with O and F groups will occur during Li-ion intercalation, which will affect their electrochemical performances. Therefore, it is necessary to investigate the structural phase transition of S-functionalized MXenes, which is helpful to understand Li storage performance and mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…10 These properties are attributed to their abundant surface chemistry, superior electronic transmission capability, and distinct hydrophilicity. 11–18 Among these applications, their role in energy domains is particularly noteworthy due to the remarkable performance offered by numerous materials within the MXene family. Nevertheless, the persisting issue of dendrite formation in batteries remains unresolved within MXene materials.…”
Section: Introductionmentioning
confidence: 99%
“…Efficient energy storage systems have always been a core topic of global interest systems have profoundly impacted daily life, with applications ranging from portable devices, electric and hybrid vehicles, to large power grids and various electronic equipment [1,2]. In the energy storage market, rechargeable lithium-ion batteries (LIBs) dominate due to their high energy 4 These authors contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…* Authors to whom any correspondence should be addressed. storage efficiency, long cycle life, and portability [1]. Since the successful exfoliation of graphene in 2004 [3], there has been widespread interest in two-dimensional (2D) materials [4], which have become a focal point of research, particularly in the field of battery materials, garnering significant attention from many researchers [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%